The Research Achievements of Dr. R. Otgonbaatar - Dashnyam, Munkh-Otgon (Tibetan Studies, 2025)
Otgonbaatar, an eminent scholar and close disciple of People’s Teacher D. Choijilsuren and National Writer, Academician Ts. Damdinsuren, graduated from the National University of Mongolia in 1978 with a degree in Mongolian Language and Literature Education. After graduation, he remained at the university as a lecturer and later joined the Institute of Language and Literature as a research fellow, where he worked until his retirement. Affectionately known among his colleagues as “Baavai” or “Otgon Baavai,” he is remembered with deep respect and fondness. This article highlights Dr. Otgonbaatar’s research experience, scholarly methods, and academic achievements. From a young age, he devoted himself to research, publishing numerous books, papers, and conference presentations. His works predominantly focus on studies related to Mongolian-Tibetan manuscripts and source materials. Эрдэмтэн Р.Отгонбаатарын эрдмийн ажил Хураангуй: Ардын багш Дагвын Чойжилсүрэн, ардын уран зохиолч, академич Цэндийн Дамдинсүрэн нарын шадар ойрын шавь Р.Отгонбаатар 1978 онд Монгол Улсын их сургуулийг монгол хэл уран зохиолын багш мэргэжилтнээр төгсөөд сургуульдаа багшаар үлдэж, төд удалгүй Хэл зохиолын хүрээлэнд эрдэм шинжилгээний ажилтнаар ажилласаар өндөр насны тэтгэвэртээ гарчээ. Хүрээлэнгийнхний маань дотночлон бас хүндэтгэн авгайлдгаар “Баавай” буюу “Отгон баавай” гуайн эрдэм шинжилгээний ажлын туршлага, арга барил, ололт амжилтын талаар энэхүү өгүүлэлд дурдах юм. Эрдэмтэн Р.Отгонбаатар идэр залуугаасаа эрдэм номын ажилд шамдаж олон ном бүтээл туурвиж, эрдэм шинжилгээний өгүүлэл илтгэл ч арвин ихийг бичиж хэвлүүлэн хэлэлцүүлсэн юм. Түүний бүтээлүүдээс ажиглахад дийлэнх хэсэг нь монгол төвөд эх бичиг сурвалж судалгааны холбоотой зүйлс бий. Түлхүүр үг: Модон бар, монгол төвөд ном хэвлэл, эртний бар хэвлэлийн тойм, гарчиг